READING MISCUES ANALYSIS ON A DYSLEXIC STUDENT OF ENGLISH STUDY PROGRAM OF FACULTY OF CULTURAL STUDIES : A CASE STUDY - PRASANTI, FRISKA ESTHI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Psycholinguistics is the study of how human can build, apply, acquire also understand the language in psychological and neurobiological way. It also deals with language disorder and it is divided into two types; acquired and developmental disorder. In this study, the writer only investigates the developmental disorder because the subject of this study suffers from developmental disorder called as developmental dyslexia. This disorder will trouble someone in reading and writing. In this situation, a dyslexic can do miscue when they read something. To investigate the miscue reading from a dyslexic the writer did miscue analysis by using Reading Miscue Inventory (RMI). The writer focuses on the miscue action during oral reading from Amelia Septiarisa. The aim of this study is to find out the types of errors from reading miscues produced by Amelia Septiarisa as a dyslexic.  This study uses qualitative approach because it analyzes the reading miscue from a dyslexic student in Faculty of Cultural Studies, Universitas Brawijaya. Case study  is applied in this study  to get the detail description from the subject. The data of this study is miscue reading from a dyslexic, Amelia Septiarisa.     This study reveals that there are five types of errors which occur in miscue analysis. Those are substitution, omission, self-correction, hesitation and repetition. The writer does not find insertion and reversal from miscue analysis process. From the test, the writer finds 2 substitutions, 4 omissions, 3 self-corrections, 50 hesitations and 11 repetitions. The writer uses the table of scoring system sheet to show the types of error showed from the subject’s utterances and gestures. In this study, the writer concludes that Amelia Septiarisa cannot read orally in loud mode. In addition, the result of this study cannot be generalized to other adult dyslexic people. Reading orally will give her hard situations and make her do miscues action during the oral reading.     The last, the writer suggests that the next researcher who wants to analyze miscue action from dyslexic can apply another tool such as Retropective Miscue Analysis (RMA) to analyze reading miscue on a dyslexic. Keywords: Dyslexia, Dyslexic, Miscue, Miscue analysis, Reading Miscue Inventory (RMI)